Capabilities and Apparent Implications of Artificial Intelligence (AI) Adoption in Nigerian Academic Libraries - AKINOLA, S. A. (University Library at a New Stage of Social Communications Development. Conference Proceedings, 2023)
Objective. This paper discusses the capabilities and implications of Artificial Intelligence (AI) in Nigerian academic libraries. The study emphasizes the importance of libraries using new technologies to improve their operations and services, especially in developing countries like Nigeria. Methods. The research conducted a literature review to examine the capabilities of AI in libraries and its impact on academic libraries. Results. Various AI tools such as natural language recognition, robotics, big data, and machine learning were identified. AI can revolutionize library services, improve information quality, increase productivity, and provide virtual assistance. However, there are challenges to the adoption of AI in Nigerian academic libraries, including high costs, resistance to change, poor network connectivity, privacy and ethical implications, and a lack of supportive cultures. To fully exploit the benefits of AI, libraries must develop plans and policies, train librarians with the necessary skills, and address the challenges associated with AI adoption. Conclusions. AI holds great advantages to enhancing library services in Nigeria, but careful planning and preparation are needed.